A Constitutional Right to Home Instruction? - Neal Devins (Washington University Law Quarterly, 1984)
This Article attempts to define the boundaries of permissible state authority in the home schooling context. The underlying thesis of this Article is that the state cannot prohibit or render meaningless the home study option. At the same time, the state has authority to insist that students taught at home learn as much as their public school counterparts. Supreme Court decisions recognize the fundamental nature of both a parent's child-rearing interest and religious freedom. Also, writings in the fields of developmental psychology and educational theory, as well as writings concerning the role of education in an open political system, recognize the parents' special interest in directing their child's education.
Keywords: Education; Constitutional law -- United States; Family law; Parent and child (Law); Public schools; United States